The DESIGN AND BUILD OF A ROCKET STATIC THRUST TEST BASED ON A RASPBERRY PI 4.0 - Pratama, Bima Anugrah; Mahfudi, Isa; Candra Widyati, Theresia Dwi Siwi (Jurnal Telkommil, 2021)
Abstract: A flying vehicle, or guided missile that gets a boost or a rapid reaction to the propellant material from the engine output is called a rocket. The Indonesian Army really needs measuring tools to determine the ability of a rocket to be made. Therefore, in this study the author will design a temperature measuring device, thrust, and temperature on a rocket with a rocket load of 1 ton. The research method used is pure experiment. This study aims to find data on temperature, thrust, and temperature on the rocket in order to find out the specifications needed so that the rocket can fly as desired. The resulting data will later be sent to the raspberry pi to be processed in order to get the results which will later be printed on paper that will be used for a research on making rockets to help the Indonesian Army in developing defense equipment in the rocket field.